Enhancing Productivity of UD Rahayu Food by Symmetrical Tofu Cutter Utilization - Erwan Adi Saputro; Rachmad Ramadhan Yogaswara; Eristya Maya Safitri (Future Science, 2021)
UD. Rahayu Food was one of pioneer on the special tofu production with soft texture called “tahu susu”. During pandemic of Covid-19, the productivity of UD. Rahayu Food was decreased and it had an impact on their sales. Optimalization of its production process by technology application would be one of the solutions for UD. Rahayu Food. The aims of this community service at UD. Rahayu Food is upgrading their productivity rate by production tools improvement. The production tool that was developed on this activity is symmetrical tofu cutter. This equipment was utilized for cutting of tofu symmetrically before being processed into “tahu susu”. Moreover, this cutter could speed up the slicing step process and their product quantity would be raised. Hopefully, provision of this symmetrical cutting tool could increase the income of UD. Rahayu Food during Pandemic Covid-19